L–H transition trigger physics in ITER-similar plasmas with applied n = 3 magnetic perturbations. (24th September 2019) - Schmitz, L.; Kriete, D.M.; Wilcox, R.S.; Rhodes, T.L.; Zeng, L.; Yan, Z.; McKee, G.R.; Evans, T.E.; Paz-Soldan, C.; Gohil, P.; Lyons, B.; Petty, C.C.; et al.
Abstract: The L – H transition power threshold P LH is observed to increase with applied n = 3 resonant magnetic perturbations (RMP) in ITER-similar-shape plasmas with balanced neutral beam torque injection in DIII-D. The increase is most pronounced with added electron–cyclotron heating: P LH increases with decreasing edge plasma collisionality as P LH / P LH-08 ( ν * ) −0.5, where P LH-08 is the 2008 ITPA multi-machine power threshold scaling. This result raises concerns for H-mode access at low edge collisionality in ITER, where RMP may have to be applied before the L – H transition to safely suppress the first edge-localized mode. Non-axisymmetric modifications with RMP include a simultaneous reduction of the radial electric field ( E r ) well depth and E × B shear. This can be attributed to increasing edge toroidal co-current rotation, and is consistent with substantially increased local long-wavelength turbulence (measured via beam emission spectroscopy). At high RMP perturbation strength the edge electric field E r reverses sign locally (becomes positive), with changes in dominant turbulence modes. Edge magnetic stochasticity provides an attractive explanation of the observed modifications, and the observed changes in toroidal rotation and E r are consistent with a simple fluid model describing radial electron current flow along stochastic fieldlines. The observed collisionality dependence of the L-mode edge electric field with applied RMP is also qualitatively consistent with this model. Reflectometry data indicate a significant reduction of the normalized L-mode radial density gradient a / L n at high RMP field with simultaneous increase in radial particle flux and electron thermal flux from power balance analysis. We conjecture that the increase of P LH with RMP results from the combined effects of reduced E × B flow shear (increasing turbulent transport levels) and toroidal/poloidal flow modulation due to edge stochasticity. Initial experiments indicate that non -resonant n = 3 magnetic perturbations lead only to relatively small changes in E r, E × B shear and fluctuation characteristics, and have less impact on the L – H transition power threshold. This motivates further exploration of the RMP spectrum dependence of P LH for possible mitigation of the observed threshold increase.